DYNAMICS OF VALUE ORIENTATIONS AND ATTITUDES OF MILITARY EDUCATION INSTITUTIONS’ CADETS - E. N. Karlova (Высшее образование в России)
The article explores the processes of transformation of Russian cadets’ motivation and value orientations during the last decade, as well as the dynamics of their motivational and value sphere throughout the period of study at military educational organizations. The analysis of scientific literature, public opinion polls and author’s own research showed the restoration of the prestige of the military profession, improving of socio-economic status of military personnel, enhancing of students’ confidence about their choice of profession. Military professional motives for enrolling in military education organization are dominating throughout the period of observation. The system of value coordinates also remains stable; cadets are generally proud of service in the Armed forces and share the norms and values of military service. The use of correspondence analysis allowed the author to identify the relationship between different motives and values and to measure the proximity between cadets of different courses in the motivation and value space. The author concludes that cadets’ motivational system is being gradually transformed as they grow up. First-year students are more attracted by pragmatic, material advantages of military service. The second, third and fourth courses take an intermediate position; this stage is characterized by the process of rethinking professional choice. Graduates have the most formed military and professional orientation, the greatest value for them is the interest to the chosen military specialty.